ウルトラフレックスメッシュカスタム® (ULTRA FLEX MESH CUSTOM®) と自家海綿骨骨髄細片を用いた顎再建の利点・欠点 - 佐々木, 朗; 吉岡, 德枝 (日本口腔外科学会雑誌, 2022)
The objects of jaw reconstruction after tumor resection were to recover the continuity of bone, to improve the esthetic problem, which was mainly facial contour, and to achieve the functional occlusion with dental prosthesis. Although there were various methods for jaw reconstruction, free vascularized bone graft has been first choice so far. Particulate cancellous bone and marrow (PCBM) and custom-made titanium mesh tray, ULTRA FLEX MESH CUSTOM® (UFMC®), have been reported as the other methods for jaw reconstruction with good outcome. The special feature of this system was to fabricate titanium-mesh tray using reconstructed 3D model by mirroring residual side of the mandible. In this way, an adequate alveolar ridge could be reconstructed with custom-made UFMC® and PCBM for the dental prosthesis with implant or denture. Besides, symmetric facial contour could be obtained. For these reasons, we have applied this system as the secondary reconstruction in malignancy and for the immediate reconstruction in benign tumor respectively.　In the present review, the clinical utilities and issues of this system were described.